2012
DOI: 10.1111/j.1365-2486.2012.02758.x
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen dynamics in grain crop and legume pasture systems under elevated atmospheric carbon dioxide concentration: A meta‐analysis

Abstract: Understanding nitrogen (N) removal and replenishment is crucial to crop sustainability under rising atmospheric carbon dioxide concentration ([CO2 ]). While a significant portion of N is removed in grains, the soil N taken from agroecosystems can be replenished by fertilizer application and N2 fixation by legumes. The effects of elevated [CO2 ] on N dynamics in grain crop and legume pasture systems were evaluated using meta-analytic techniques (366 observations from 127 studies). The information analysed for n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
90
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 111 publications
(97 citation statements)
references
References 46 publications
(70 reference statements)
4
90
1
2
Order By: Relevance
“…Whether it is economic for the farmer to carry out a late application of nitrogen fertilizer depends on the price incentives for wheat quality (Angus and Fischer, 1991) and the climate and agronomic situation. Rising atmospheric CO 2 concentrations are likely to increase grain yield but reduce grain protein concentration (Lam et al, 2012). Comparison between elite wheat cultivars reveals a tradeoff between yield and grain protein concentration (Barraclough et al, 2010).…”
Section: Photosynthesis In the Context Of The Canopymentioning
confidence: 99%
“…Whether it is economic for the farmer to carry out a late application of nitrogen fertilizer depends on the price incentives for wheat quality (Angus and Fischer, 1991) and the climate and agronomic situation. Rising atmospheric CO 2 concentrations are likely to increase grain yield but reduce grain protein concentration (Lam et al, 2012). Comparison between elite wheat cultivars reveals a tradeoff between yield and grain protein concentration (Barraclough et al, 2010).…”
Section: Photosynthesis In the Context Of The Canopymentioning
confidence: 99%
“…the amount of N fixed per unit nodule and time (Lam et al, 2012;Rogers et al, 2009), or through a greater proportion of legumes in the system (Newton et al, 2006;Reich et al, 2006). In a long-running free air carbon dioxide enrichment (FACE) experiment in Switzerland (the Swiss FACE), there was a strong stimulation of BNF in the early years of enrichment with the sum of the physiological and species proportions effects resulting in a 50 % increase in BNF (Hartwig and Sadowsky, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, any factor that might modify biological N fixation (BNF) has direct interest for agricultural production as well as environmental issues such as N emissions and carbon storage (De Deyn et al, 2009). One such factor is the increasing concentration of CO 2 in the atmosphere (Dolman et al, 2010) which has been shown to have the potential to modify BNF (Lam et al, 2012;Reich et al, 2006;. BNF is arguably of increasing importance under elevated CO 2 (eCO 2 ) as additional N (through changes in N cycling, fertilization or BNF) is required to maintain C / N ratios in the ecosystem and ensure functions such as photosynthesis and decomposition continue or are increased (Hartwig and Sadowsky, 2006;Zanetti et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…De fato, análises quantitativas de diferentes estudos mostraram que o elevado CO2 estimula o rendimento e a biomassa de plantas C3 não-leguminosas, leguminosas e de plantas C4 em 11-31%, 14-54%, e 18-27%, respectivamente (Lam et al, 2012). Como os tratamentos com aquecimento demonstraram uma maior taxa da assimilação de CO2 do que o controle (Bianconi, 2014), acredita-se que o fator temperatura tenha sido o principal estimulador do crescimento vegetal e produção de biomassa, interagindo positivamente com o fator CO2 de modo a aumentar o teor de C foliar nos tratamentos com elevado CO2.…”
Section: Discussão (Experimento Ii)unclassified
“…Por isso, as leguminosas, em especial, são capazes de alcançar um grande aumento na produtividade e manter sua taxa C/N no tecido sob elevado CO2 ao conseguirem alocar o C adicional nos nódulos fixadores de N, ampliando a disponibilidade deste nutriente para investimento no seu crescimento total (Lam et al, 2012;Leakey & Lau, 2012). Embora as plantas C3 disponham da fonte adicional de N2 atmosférico e tenham dado indícios de utilizar esta outra fonte de acordo com os dados isotópicos de 15 N, a tendência no acúmulo de N no tecido foliar vegetal ao longo do experimento não se mostrou significativamente discrepante entre as duas espécies.…”
Section: Discussão (Experimento Ii)unclassified